Tingkat Kesamaan Tanaman Nilam Hasil Fusi Protoplas Berdasarkan Morfologi dan Anatomi Daun - Haryudin, Wawan; Syukur, Cheppy; Nuryani, Yang (Perhimpunan Biologi Indonesia, 2002)
ABSTRACTSimilarity Level of Patchouli oil from Protoplast Fusion based on Morphology andAnatomy Leaves. Protoplast fusion between Aceh patchouli (Pogostenton cablin Benth)Tapak Tuan 75 clone and java patchouli (Pogostemon heyneanus Benth) Girilaya clone gonegenotypes variation. The aim of this experiment was to examine the similarities ofmorphology and anatomy of leaves. The experiment was inducted at laboratory and greenhouse of the Indonesian Spice and Medicinal Crops Research Institute from February to July2001. The parameters observed were the number of leaves length, leaves width and leafthickness, the number of oil cell, stomata and trachoma index. Analysis cluster was used toanalysis the data with single linkage method and Euclidean distance concept. The resultshowed that the leaves length, width, and thickness have close similarity with Tapak Tuan 75.The similarity level of genotype from protoplast fusion was 62.68 to 83.27, the parent TapakTuan 75 was 61.53 and the parent Girilaya 58.69. The highest numbers of oil cell was showedby clone 9 I1 4 (10.55) and the lowest was clone ( IV 14 (2.93).Key words: Pogostemon sp., similarity, protoplast fusion, morphology, anatomy, leaves.